Learning from laughter: Implicit Religion, satire, and power in two British TV situation comedies - Spoliar, Lucy (Journal of beliefs and values, 2022)
This article explores how Implicit Religion might be operationalised in research on popular culture, and specifically on the British TV sitcom. This discussion understands comedy and satire as powerful tools for articulating and contesting stereotypical designations of identity and power within a particular cultural and sociopolitical framework. Where religious characters appear in British TV sitcoms, they are often portrayed as anomalous, hinting at the assumed ‘implicit secularity’ of the audience. However, in the British context, it can be difficult to disentangle religion and the secular. Taking The Vicar of Dibley (1994 to 1998) and Citizen Khan (2012 to 2016) as case studies, this article compares portrayals of Christian and Muslim communities in British TV sitcoms. This facilitates a discussion of certain double standards in terms of the ways in which these two religious traditions are represented, and what is satirised and ‘taken seriously’ in each case. These double standards are examined with reference to historical differences in status between Christianity and Islam in the British context. This article lays the groundwork for further research on the ways in which humour in popular culture enhances our understanding of operations of Implicit Religion in relation to power within a particular national context.